2014
DOI: 10.3727/096504013x13775486749218
|View full text |Cite
|
Sign up to set email alerts
|

MiR-138 Induces Renal Carcinoma Cell Senescence by Targeting EZH2 and Is Downregulated in Human Clear Cell Renal Cell Carcinoma

Abstract: MiR-138 has been shown to be downregulated in various cancers, including head and neck squamous cell carcinoma (HNSCC) and clear cell renal carcinoma (ccRCC). In the present study, we aimed to reveal the mechanism of miR-138 induction of senescence in renal carcinoma cells and identify its specific target genes. We used qRT-PCR to analyze miR-138 expression levels in renal carcinoma cell lines and ccRCC samples. The activity of β-galactosidase was measured for functional analysis after miR-138 mimic transfecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 22 publications
2
39
0
1
Order By: Relevance
“…To the best of our knowledge, the present study is the first to demonstrate that miR-138 expression is significantly downregulated in cervical cancer tissues and cell lines, and that low miR-138 expression is negatively associated with advanced FIGO stage and lymph node metastasis. In addition, miR-138 has been previously reported to function as a tumor suppressor in numerous malignancies by targeting various molecules (13)(14)(15)(16)(17)(18)(19). For cervical cancer, a study showed that miR-138 could significantly inhibit HeLa cell migration by targeting required for meiotic nuclear division 5 homolog A (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the present study is the first to demonstrate that miR-138 expression is significantly downregulated in cervical cancer tissues and cell lines, and that low miR-138 expression is negatively associated with advanced FIGO stage and lymph node metastasis. In addition, miR-138 has been previously reported to function as a tumor suppressor in numerous malignancies by targeting various molecules (13)(14)(15)(16)(17)(18)(19). For cervical cancer, a study showed that miR-138 could significantly inhibit HeLa cell migration by targeting required for meiotic nuclear division 5 homolog A (29).…”
Section: Discussionmentioning
confidence: 99%
“…miR-138, a family of microRNA precursors, has been reported to function as a tumor suppressor in a variety of human cancers, including renal carcinoma (13), non-small lung cancer (14), colorectal cancer (15), neuroblastoma (16), esophageal squamous cell carcinoma (17), nasopharyngeal carcinoma (18) and hepatocellular carcinoma (19). However, the role and the molecular mechanisms of miR-138 in cervical remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…36 EZH2 is under the regulatory control of several miRs, including but not limited to miR-26a, miR-98, miR-101, miR-124, and miR-138. 9,37,38 The best characterized of these is miR-101. 39 Consistent with the effect of miR-101 in inhibiting EZH2 translation, we observed a profound increase in EZH2 protein in podocytes exposed to an oligonucleotide inhibitor of this miR.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic-driven gene expression profiles are dynamic, and, therefore, the complexity added due to obesity (59) and diabetes (126) needs to be evaluated systematically. (1,25,28,32,37,55,57,66,74,81,88,90,93,107,108,110,117,124,137,155,156,162). Studies examining the upstream and downstream regulation of miRNAs on oxidative stress in human disease are recently becoming available.…”
Section: Epigenetic Modification In Renal Carcinomamentioning
confidence: 99%